The micro-dynamics of agency, metadata: 2021-2024 - Brett, Roderick Leslie (UK Data Service, 2025)
Our research in Colombia, Lebanon, and Northern Ireland provides granular-level insights into how civilians endure ‘peace’. At the micro-level of individual interactions, people have to ‘get on with it’, putting food on the table, getting kids to school and sustaning daily tasks. This often occurs against a backdrop of continuing threats of violence, stigmatisaton and difficult economic circumstances. We have used daily pattern of life interviews, community mapping and visualisation, and walking interviews to try to capture individual strategies at the micro-level and understand how lives are lived where peace is either fragile or elusive. We spoke to over 350 civilians about their experiences and daily lives and this report sets out our principal findings and their policy implications. Approximately 2 billion people live in regions plagued by violent conflict (World Bank 2017); within a decade, half the global population will live in countries affected by violence and instability. A key factor shaping global insecurity is that the conventional means for bringing an end to armed conflict do not deliver sustainable peace: around 50% of peace settlements collapse within 10 years. Even when peace holds, its quality is often poor. Recidivism and poor-quality peace represent significant global security concerns, as pervasive post-accord political/criminal violence, poverty and exclusion continue to blight the lives of people living in fragile societies. Peace tends to reach conflict-affected communities slowly, if at all, and ordinary people must get on with living, providing for their families where jobs and state/government support are often absent. They must navigate complex, often traumatic relations between neighbours/authorities, where mutual distrust and discrimination and the legacies of war mean that people experience the present and imagine the future through the societal cleavages and violent memories of the past. This research aims to understand how civilians face the challenges of failed/failing peace and how they navigate the causes, consequences and legacy of intergroup political violence when formal, top-down interventions do not reach them (RQ1). The project will create innovative original empirical and theoretical data and develop the concept of the Micro-Dynamics of Post-Conflict Intergroup Relations, describing the everyday tactical agency, mechanisms and narratives that individuals, communities and groups employ in order to cope with the legacy of political violence and learn to co-exist with or challenge their former 'enemies' (RQ2). The research will evaluate whether and, if so, how ordinary people play a role in sustaining peace when formal interventions do not reach them, or, if they do, generate limited effect (RQ3). Employing a cutting-edge participatory, co-production methodology of qualitative and quantitative methods, such as embedded ethnography, life histories, map-making, walking, photography, Nvivo, the project will develop a systematic evidence base of everyday tactics and strategies and the factors that shape civilians' ability to craft them. The project explores how factors such as inequality, economic/political exclusion and criminal/political violence affect civilian capacity to levy everyday micro-practices and their subsequent influence upon peacebuilding, intergroup coexistence and reconciliation. Given our focus upon local knowledge and everyday tactics/strategies, 3 country Partners and community stakeholders will participate from the outset through planned and costed activities and strategies to develop a robust theoretical model informed by stakeholders themselves. This model will advance theoretical insights by developing innovative concepts, such as post-accord civilian social entrepreneurship and individual and intergroup micro-social contracts, significantly advancing scholarship and leading to academic impact. Through Knowledge Exchange (KE) with funded direct Partners and wider networks of policymakers and scholars, we will contribute substantially to policy/practitioner knowledge of the factors shaping the stability of political settlements, the likelihood of recidivism and the quality of peace. Working with Partners, PolicyBristol and Durham Policy Hub, we will organise learning events, disseminating evidence-based knowledge of how local actors can sustain or challenge peace from below. We thus expect to facilitate considerable economic/societal impact through KE and lessons learned with peacebuilding/development practitioners. As an integrated whole then, the research will yield academic and economic/societal impact, ultimately reframing key debates, strengthening local capacities, building policy-relevant conceptual models and shaping policy and practice